Climate change adaptation measures in territorial planning documents - Sadkovskaya Oxana Ye. (Архитектон)
Issues in adaptation of cities to the consequences of climatic changes are relevant for the Rostov region as stated in the approved regional adaptation plan for climate change. The article analyzes the effects of climate change that will have a significant impact on the comfort and safety of urban areas in the region. The possibilities of adapting urban areas to the consequences of climate change in the Rostov region are assessed. One of the important steps in adapting cities to climate change is to amend territorial planning documents. To this end, regional urban planning standards will be developed to offset the negative consequences of climatic changes for the urban environments. A list of measures that could be taken to compensate for the negative consequences of climate change at the level of the settlement system for inclusion in the territorial planning scheme of the Rostov region. A list of climatic change compensation indicators is proposed for inclusion in the regional urban planning standards of the Rostov region.